Benefits of the Hydrophobic Surface for CH3NH3PbI3 Crystalline Growth towards Highly Efficient Inverted Perovskite Solar Cells - Yang Li; Zheng Xu; Suling Zhao; Dandan Song; Bo Qiao; Youqin Zhu; Juan Meng (Molecules, 2019)
In inverted perovskite solar cells (PSCs), high-quality perovskite film grown on hole-transporting material (HTM) with pinhole-free coverage and a large grain size is crucial for high efficiency. Here, we report on the growth of pinhole-free and large grain CH3NH3PbI3 crystals favored by a hydrophobic small molecular HTM, namely, 4,4′-Bis(4-(di-p-toyl)aminostyryl)biphenyl (TPASBP). The hydrophobic surface induced by TPASBP suppressed the density of the perovskite nuclei and heterogeneous nucleation, thus promoting the perovskite to grow into a dense and homogeneous film with a large grain size. The CH3NH3PbI3 deposited on the TPASBP exhibited better crystallization and a lower trap density than that on the hydrophilic surface of indium tin oxide (ITO), resulting in a significant reduction in carrier recombination. Combined with the efficient hole extraction ability of TPASBP, a high efficiency of 18.72% in the inverted PSCs fabricated on TPASBP was achieved.